2016
DOI: 10.5114/wiitm.2016.64981
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic primary tumour in incurable metastatic colorectal cancer: is there a role for surgical resection prior to systematic therapy or not?

Abstract: IntroductionThe role of the resection of asymptomatic primary colorectal cancer in patients with incurable disease is questionable.AimTo evaluate the impact of the resection of asymptomatic primary tumour on overall survival in patients with unresectable distant metastases.Material and methodsPatients treated in the National Cancer Institute, Lithuania, in the period 2008–2012, were selected retrospectively. The main inclusion criteria were: metastatic colorectal cancer (mCRC), endoscopically and histologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Figure 1 shows the study flow diagram. Seventy‐seven comparative studies fulfilled the inclusion criteria of this meta‐analysis [2, 4–8, 10–27, 30–50, 69–100]. There were 159,991 patients for analysis, including 94,745 (59.2%) in the PTR group and 65,246 (40.8%) in the PTI group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the study flow diagram. Seventy‐seven comparative studies fulfilled the inclusion criteria of this meta‐analysis [2, 4–8, 10–27, 30–50, 69–100]. There were 159,991 patients for analysis, including 94,745 (59.2%) in the PTR group and 65,246 (40.8%) in the PTI group.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, not every patient will be a candidate for surgery, and among patients, the benefits of surgery will be different. Studies which performed multivariate analysis to determine which factors were associated with survival in patients with unresectable colorectal cancer, in addition to PTR, identified the following independent prognostic variables: primary tumor differentiation grade [4, 5, 11, 21–23, 25, 28, 29, 48], number of metastatic sites [2, 12, 14, 18, 21, 22, 25, 47, 66], primary tumor location [4, 6, 12, 22, 23, 25, 28, 66], extent of metastatic liver involvement [32, 48, 49, 75, 81, 89, 94], administration of chemotherapy [4, 14, 20, 24, 32, 39, 48, 49, 93], administration of anti‐VEGF therapy [2, 13, 21, 23], CEA levels [5, 12–14, 28, 32], age [4, 6, 18, 22, 25, 28, 29], Eastern Cooperative Oncology Group performance status (ECOG‐PS) [4, 14, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 However, other studies have demonstrated a survival benefit in primary tumor resection among patients with metastatic colorectal cancer. [30][31][32] Current randomized studies are investigating the utility of upfront primary surgical resection (CAIRO4, 33 SYNCHRONOUS, 34 Korean NCT01978249 35 ), the results of which are greatly anticipated to further elucidate this question.…”
Section: F I G U R Ementioning
confidence: 99%
“…Surgery is the cornerstone treatment that relieves symptoms associated with obstruction, perforation or bleeding in patients with colorectal cancer who have an obstructed bowel. In patients with unresectable metastases and intact primary tumours that do not obstruct the bowel, systemic chemotherapy is the treatment of choice 2 . However, a large percentage of cancer patients eventually relapse and develop drug resistance 3,4 .…”
Section: Introductionmentioning
confidence: 99%